The illustrated Dictionary of Earth Sciences - Earth Science (Bloomsbury Books, 1994)
The illustrated Dictionary science form a series of highly visual reference books for children. each volume contains about 850 entries on an individual science.
Keywords: Earth Sciences; General; Science